Graphitic carbon nitride/antimonene van der Waals heterostructure with enhanced photocatalytic CO2 reduction activity. (20th July 2022) - Zhang, Jinfeng; Fu, Junwei; Dai, Kai
Abstract: Photocatalytic reduction of CO2 into valuable fuels is one of the potential strategies to solve the carbon cycle and energy crisis. Graphitic carbon nitride (g-C3 N4 ), as a typical two-dimensional (2D) semiconductor with a bandgap of ∼2.7 eV, has attracted wide attention in photocatalytic CO2 reduction. However, the performance of g-C3 N4 is greatly limited by the rapid recombination of photogenerated charge carriers and weak CO2 activation capacity. Construction of van der Waals heterostructure with the maximum interface contact area can improve the transfer/seperation efficiency of interface charge carriers. Ultrathin metal antimony (Sb) nanosheet (antimonene) with high carrier mobility and 2D layered structure, is a good candidate material to construct 2D/2D Sb/g-C3 N4 van der Waals heterostructure. In this work, the density functional theory (DFT) calculations indicated that antimonene has higher carrier mobility than g-C3 N4 nanosheets. Obvious charge transfer and in-plane structure distortion will occur at the interface of Sb/g-C3 N4, which endow stronger CO2 activation ability on di-coordinated N active site. The ultrathin g-C3 N4 and antimonene nanosheets were prepared by ultrasonic exfoliation method, and Sb/g-C3 N4 van der Waals heterostructures were constructed by self-assembly process. The photoluminescence (PL) and time-resolved photoluminescence (TRPL) indicated that the Sb/g-C3 N4 van der Waals heterostructures have a better photogenerated charge separation efficiency than pure g-C3 N4 nanosheets. In-situ FTIR spectroscopy demonstrated a stronger ability of CO2 activation to *COOH on Sb/g-C3 N4 van der Waals heterostructure. As a result, the Sb/g-C3 N4 van der Waals heterostructures showed a higher CO yield with 2.03 umol g −1 h −1, which is 3.2 times that of pure g-C3 N4 . This work provides a reference for activating CO2 and promoting CO2 reduction by van der Waals heterostructure.